Prevalence and Factors Associated With Utilization of HIV Self Testing Among Students of Universities in South Western Uganda. - Namande, Marvice; Kabami, Jane; Agaba, Dickson; Asiimire, Allion; Natwijuka, Andrew; Kebeyi, Irene; Mugumya, Robert; Beinempaka, Florence; Muhumuza, Allan (Student's Journal of Health Research Africa, 2021)
Background HIV self-testing (HIVST) is globally accepted as an important complement to existing HIV Counseling and Testing approaches. This study aimed at determining the prevalence and factors associated with the utilization of HIV self-testing among university students of Southwestern Uganda. Methods An online cross-sectional study design that used the quantitative approach was conducted purposively among 356 university students of Kampala International University (KIU) and Mbarara University of Science and Technology (MUST) in Southwestern Uganda between 12th August 2020 and 31st August 2020. Mapping different course leaders in launching the Google form link that contained the structured questionnaires in their respective formal class WhatsApp groups for enrolling potential participants. Descriptive analysis of numeric data was summarized in means with standard deviations and presented using tables. Descriptive analysis of categorical data was summarized in frequencies, proportions and presented using tables. Association between independent and dependent variables was assessed using the Chi-square test (X2) for bivariate analysis in SPSS IBM version 20. Results Of the 356 participants, the study had 57.3% of the participants from KIU and 42.7% were from MUST. The study found that university students who had ever self-tested were 43.2%. Socio-demographic variables associated with utilization of HIV self-testing were the student’s year of study (p = 0.007), having a sexual partner (p = 0.012), and place of residence (p = 0.000). Conclusions The study demonstrates low levels of utilization of HIV self-testing among University students in association with a number of factors that include how they are aware of HIV self-testing, places of their residence, having a sexual partner.